THE IMPACT OF THE COVID-19 PANDEMIC AND THE DROUGHT ON THE PRICES OF THE MAIN AGRICULTURAL PRODUCTS OF ANIMAL ORIGIN IN ROMANIA - BADAN (VOICILA), Daniela Nicoleta; PETRE, Ionut Laurentiu (Economy and Sociology, 2021)
Globally, the pandemic installed by the coronavirus has led to a change in the way business is conducted. In the context of the economic crisis knocking on the door, the states of the world are trying to take the most severe measures to mitigate the effects of this epidemic. One sector of the economy that needs to be protected is agriculture, because it provides the much-needed food for everyone. The role of farmers is very important in this equation, as they provide the necessary food stabilizing stocks of food that can be depleted faster. In this paper we want to determine the possible impact that the drought and the overlap of the COVID pandemic on it may have on the prices of agricultural products of animal origin in Romania. In this context, the level of prices in the first half of the previous year was compared with the level of prices in the first half of the current year, in order to be able to determine, from a statistical point of view, whether there are significant differences. It was found that for five of the six products analyzed, the prices in the first half of 2020 were higher than in the first half of 2019. Following this analysis, the correlation coefficients between the price level and the precipitation level were determined, and subsequently between the price level and the market demand, the latter influenced by the pandemic. It was found that both phenomena indirectly influenced the prices of agricultural products of animal origin.